Pengembangan Media Video Animasi Berbasis Prezi Materi Organ Tubuh Manusia pada Siswa Kelas IV Sekolah Dasar - Ramadamayanti, Risanda; Vebriani, Veronika; Setiyawan , Hery (Indo-MathEdu Intellectuals Journal, 2025)
The use of traditional learning media such as books and LKPD often causes boredom and decreased interest in learning among students. Prezi-based animated video technology is an innovative solution to visualize abstract materials such as human organs. Developing appropriate and effective animated video media to improve the understanding of 4th grade elementary school students on human organs. Research and development (R&D) uses the ADDIE model (Analysis, Design, Development, Implementation, Evaluation). Data collection techniques are carried out through literature studies of previous and relevant scientific sources. Validation involves media experts, material experts, teachers, and students. Data are collected through questionnaires, observations, interviews, and tests. The media is declared very appropriate by media experts and material experts. Student responses are very positive. The effectiveness of the media is proven by the increase in the average pretest to posttest score. Prezi-based animated video media is effective in improving student understanding and is appropriate to be implemented in science learning